Practicing the Family : The Doing and Making of Family In, With and Through Social Work and Education - Sabine Bollig; Lisa Groß (transcript, 2024)
How »family« is construed on a material and discursive level has gained increasing interest among educational and social work professionals. The contributors to this volume address that question in relation to the diverse everyday practices of »doing family« by its heterogeneous members. The contributions build a transdisciplinary bridge between research on family life on the one hand and research on the formatting of family in welfare state contexts on the other. Fundamental to this is a decentred and fluid understanding of family that conceives itself as a contested set of relational activities in people's everyday lives that are socially recognized as »familial«.